AN ERROR ANALYSIS ON SUBJECT-VERB AGREEMENT IN NARRATIVE WRITING TEXT MADE BY SENIOR HIGH SCHOOL STUDENTS - Solehah, Sitti Anis Jumatus; Listyowati, Rini; Daril Hanna, Ina (Universitas Islam Lamongan, 2023)
This study aims to find out and analyze students' mistakes in writing narrative text and what causes these mistakes. The method used in this research is a qualitative research design with a case study method by applying descriptive analysis. In this study, the object being analyzed was the subject-verb agreement error in writing narrative text in class XI IPA 2 of the tenth grade of MA Miftahul Qulub Polagan Galis Pamekasan. The problem of this research is to find the types of errors that commonly, the causes of errors, and the frequency of errors that students made in using subject-verb agreement in writing narrative text. The errors are classified into four primary groups based on the surface strategy taxonomy of superficial strategies cited by (Irwansyah,2017): omission, addition, misformation, and misordering errors. The researcher found those errors in the students' work in writing narrative text. It can be seen that each student made one to three errors, which are omission, addition, and misformation errors. From the results of the frequency of omission errors 53%, 39% addition errors, 7% misformation errors, and 0% misordering errors. errors that are often made by students, namely the 53% omission error has a higher percentage than the errors that occur in other types. Based on the results of this research, the researcher hopes that it will become important data for the language community, especially those who are interested in analyzing errors in English lessons. This research is expected to increase the reader's knowledge about good sentence patterns in the structure of the English language. Keywords: Analysis error, subject-verb agreement, writing narrative text